Pengaruh Variasi Nilai Resistor pada Regulator terhadap Pengisiaan Baterai 12 V, 50 A : Penelitian - Pasaribu, Sabar; Ginting, Tinus; Surbakti, Adnan; Sembiring, Resep; Harahap, Astro Julida (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The purpose of this study is to find out how much influence the replacement of lower resistor resistance values ​​(6 and 8 0hm) with rotations of 1000, 2000, 3000, 4000 rpm has on battery charging, and to find out how much influence the replacement of higher resistor resistance values ​​(13 and 15 0hm) with rotations of 1000, 2000, 3000, 4000 rpm has on battery charging. From the background, the regulator charging system is a system that is very much needed in four-wheeled vehicles to meet the needs of battery current when the engine is running, because when the engine is running, especially gasoline engines, it really needs battery current for the continuity of the system to work, the method used in this study is the literature study method and direct testing method as well as recording the results and analyzing them theoretically based on observations. The results obtained are experimental research on the resistor resistance value below the standard size, the charging voltage at 1000 rpm engine speed is above the battery voltage, if the engine speed is increased higher then overcharging will occur (excessive charging) then the battery will be damaged where the charging voltage at idle speed is sufficient for the battery voltage, and does not exceed the battery limit voltage when the rotation reaches 4000 rpm, which is 14.5 volts, while the battery limit voltage is 14.8 volts.